Wildlife tourism as a tool for jaguar conservation in the Pantanal - Tortato, Fernando Rodrigo (2018)
This study evaluated the relationship of the jaguar with the main economic activities of the Pantanal, cattle ranching and ecotourism. For ecotourism, the jaguar represents one of the greatest attractions, yet for cattle ranching it often represents damage, as it can attack the herd. Understanding this antagonistic relationship about the jaguar is essential to establishing conservation strategies for this species in the Pantanal. In the first chapter, we evaluated the advances and barriers for the development of wildlife observation tourism in the Pantanal. As a further step forward, the state resolutions that establish rules for this activity were considered. The absence of management plans and inspection of protected areas was considered the main barrier. In the second chapter, we evaluated on a similar spatial scale, how much a jaguar population represents in revenue for seven ecotourism lodges and damage to cattle ranches. Interviews were conducted with tourists in order to assess the feasibility of a system to compensate for the damage through donations from ecotourism. The main results were that the jaguar population represents 52 times more revenue than damage and that 80% of tourists are willing to cooperate with the compensation system. With this, these results allow for the integration of these two economic activities in favor of regional conservation of the jaguar. In the appendices we present a letter correcting some published misconceptions about protected areas in the Pantanal. It is cited the booklet published during the doctorate, which contributes to the dissemination of science in the Pantanal. In summary, this thesis allows evaluate in different aspects and scales the importance of ecotourism for jaguar conservation in the Pantanal.